Development of Historical Learning Media Based on Virtual Reality of The National Awakening Museum - Suryani, Mira; Sakti Rusidiawan, Rispansah; Rosadi, Rudi (Inform : Jurnal Ilmiah Bidang Teknologi Informasi dan Komunikasi, 2022)
In history learning, visits to locations such as museums or other historical places in the pandemic Covid-19 situation are minimal. However, learning activities must be continued, and the existing conventional learning media in the pandemic scenario are deemed less to provide the experience. Based on previous learning experiences, an obligation to transfer knowledge from museum managers, and technological developments related to virtual reality, supports an idea to develop a museum national awakening virtual reality. This VR application is expected to become an alternative historical learning medium. This study aims to create a museum national awakening VR based on 360-degree images of the museum location. The multimedia development life cycle (MDLC) is chosen as the method used in developing the proposed VR application. The procedure consists of six steps: defining the concept based on on-site observation and interviews with the manager, creating the design, collecting the material, assembling materials and interactions with code, testing the proposed application, and distributing the system. The proposed virtual tour application has been successfully developed following the methodological principles chosen. It is also supported by a series of observations in the field using a cognitive walkthrough approach. The application was then reviewed by five experts: historians, multimedia, and learning experts. The location detailing is perfectly captured, including all the objects shown in each museum room. The quiz feature also strengthens the VR application as the learning medium, but it needs to be developed further in the evaluation section.